RESPON PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) VARIETAS FLAMINGO AKIBAT PERLAKUAN MACAM MEDIA TANAM DAN KONSENTRASI PUPUK PELENGKAP CAIR BAYFOLAN - Shinta Nurhasanah; Ai Komariah; Roni Assafaat Hadi; Kovertina Rakhmi Indriana (Sekolah Tinggi Pariwisata Mataram, 2021)
Abstract Pakcoy is a popular vegetable, besides being easy to cultivate, it also contains many benefits. In 2017-2019 Pakcoy production decreased. This is caused by several factors, one of which is the use of planting media and fertilization. The purpose of this experiment was to determine the interaction between the composition of the growing media and the concentration of complementary fertilizers on the growth and yield of pakcoy plants. This experiment was carried out in Sindanglaya Village, Tanjungsiang Disrtict, Subang Regency with an altitude of 700 meters above sea level an average daily temperature of 27.27ºC. The experiment was carried out in July-August 2020. The design used was a factorial randomized block design (RBD) consisting of two factors and repeated twice. The first factor is the composition of the planting medium (M) which consists of four levels, namely: m0 = (soil), m1 = (soil + sheep manure), m2 = (soil + cow manure), m3 = (soil + manure ) chicken). The second factor is the concentration concentration of bayfolan liquid complementary fertilizer (P) which consists of four levels, namely: p1 = (1 ml L-1), p2 = (2 ml L-1), p3 = (3 ml L-1), p4 = (4 ml L-1). The experimental results showed the interaction of planting media and bayfolan liquid complementary fertilizers on wet weight. Soil planting medium + chicken manure (m3) and liquid complementary fertilizer 2 ml L-1 (p2) showed the best results, namely 1.07 kg.